A reconstruction-based mode separation method of Lamb wave for damage detection in plate structures. (15th February 2019) - Zhou, Kai; Zheng, Yuebin; Zhang, Jiaqi; Xu, Xinsheng; Ma, Shuyi; Wu, Zhanjun
Abstract: This paper presents a new method to separate multi-mode signal of Lamb wave through reconstruction of pure mode basis signals calculated based on phase and group velocity. Individual signal of each mode contained in multi-mode signal can be obtained and analyzed by mode separation. Simultaneously, the hidden damage scattering signal can be extracted after removing the undesired signal. Two simulations are conducted on aluminum plates as examples to demonstrate the procedure of mode separation in detail. The first one models Lamb wave propagating in an aluminum plate without damage to separate each mode step by step. Extraction of damage scattering signal through mode separation is presented with the other simulation conducted on a damaged aluminum plate. Also an experiment is designed to example the applicability of this method. The results of both simulations and experiment verify the validity and accuracy of this method. This mode separation method provides a potential baseline free approach for damage detection using Lamb wave.